1959
DOI: 10.2134/agronj1959.00021962005100060014x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Reniform Nematode on Yield, Plant Characters, and Fiber Properties of Upland Cotton1

Abstract: Synopsis The reniform nematode reproduced abundantly on cotton and caused serious injury to all varieties tested. It caused reduction in yield of lint, delay in maturity, reduction in size of boll, and, in some years, reduction in lint percent. No effect was noted on seed size, fiber length, fiber strength, or fiber fineness. Although the nematode increased wilt development on wilt‐susceptible varieties, it did not increase wilt on resistant varieties developed in other areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
2
17
2
Order By: Relevance
“…Research quantifying how various aspects of plant growth and development are impacted by reniform nematode parasitism among a diverse group of cotton genotypes under field conditions is limited. Jones et al (1959) reported that fumigation to suppress reniform nematode populations in field plots produced cotton yield increases, earlier maturity, and larger bolls. Lint percentage was inconsistently increased as a result of suppressing reniform nematodes in their research.…”
mentioning
confidence: 99%
“…Research quantifying how various aspects of plant growth and development are impacted by reniform nematode parasitism among a diverse group of cotton genotypes under field conditions is limited. Jones et al (1959) reported that fumigation to suppress reniform nematode populations in field plots produced cotton yield increases, earlier maturity, and larger bolls. Lint percentage was inconsistently increased as a result of suppressing reniform nematodes in their research.…”
mentioning
confidence: 99%
“…reniformis infection include plant stunting, suppressed root growth, nutritional deficiencies, fruit abortion and delayed maturity (Koenning et al, ). Rotylenchulus reniformis infection affects cotton production by reducing seed cotton yield, boll size and lint percentage (Cook, Robinson, & Namken, ; Jones, Newsom, & Finley, ). Management of R .…”
Section: Introductionmentioning
confidence: 99%
“…Rotylenchulus reniformis is an obligate, sedentary semi‐endoparasite in which vermiform preadult females penetrate the host root system where they establish a feeding site in the stele (Agudelo, Robbins, Stewart, Bell, & Robinson, ; Koenning et al., ; Robinson, Inserra, Caswell‐Chen, Vovlas, & Troccoli, ). Rotylenchulus reniformis infection of cotton affects production by reducing seed cotton yield, boll size and lint percentage (Cook, Robinson, & Namken, ; Jones, Newsom, & Finley, ). Nematode infection symptoms may not be apparent due to the uniformity of symptoms across the field; however, symptoms can include plant stunting, suppressed root growth, nutritional deficiencies, fruit abortion and delayed maturity (Koenning et al., ).…”
Section: Introductionmentioning
confidence: 99%